Sistemas de costos en el proceso productivo del sector camaronero del cantón Chone - Mendieta Sánchez, Jessenia Florentina (2022)
This research work called cost systems in the production process of the shrimp sector of the Chone canton, aims to carry out a cost system in the production process of the shrimp sector. Aquaculture and shrimp fishing are industries that have gained dynamism and prominence within the country's economy, and cost information becomes increasingly crucial, since product prices are set by the market and not by producers.............